3D Metal Printing Technology - Duda, Thomas; Raghavan, L. Venkat (IFAC-PapersOnLine, 2016)
3D Printing or Additive manufacturing is a novel method of manufacturing parts directly from digital model by using layer by layer material build-up approach. This tool-less manufacturing method can produce fully dense metallic parts in short time, with high precision. Features of additive manufacturing like freedom of part design, part complexity, light weighting, part consolidation and design for function are garnering particular interests in metal additive manufacturing for aerospace, oil & gas, marine and automobile applications. Powder bed fusion, in which each powder bed layer is selectively fused by using energy source like laser, is the most promising additive manufacturing technology that can be used for manufacturing small, low volume, complex metallic parts. This review presents overview of 3D Printing technologies, materials, applications, advantages, disadvantages, challenges, economics and applications of 3D metal printing technology.